2009
DOI: 10.1080/00016340902859315
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress but not endothelial dysfunction exists in non‐obese, young group of patients with polycystic ovary syndrome

Abstract: Oxidative stress is prominent while endothelial dysfunction does not exist in young, non-obese patients with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
44
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 33 publications
10
44
1
1
Order By: Relevance
“…This is in agreement with previous reports [15][16][17] which have reported increased oxidative stress even in lean PCOS women. Oxidative stress was previously linked to obesity commonly seen in these women [13,18].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This is in agreement with previous reports [15][16][17] which have reported increased oxidative stress even in lean PCOS women. Oxidative stress was previously linked to obesity commonly seen in these women [13,18].…”
Section: Discussionsupporting
confidence: 94%
“…Oxidative stress was previously linked to obesity commonly seen in these women [13,18]. However, a few other studies have found increase in oxidative stress even in lean PCOS women [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raised SOD might be an over expression of this enzyme as a compensatory adaptive response for the increased demand for dismutation of superoxide radical. Our findings are in accordance with the studies by Sabuncu et al [13], Kuscu et al [29], Azzawie et al [30] and Mohan et al [31] where they reported the presence of oxidative stress in PCOS patients.…”
Section: Discussionsupporting
confidence: 93%
“…13 In the present study MDA levels were found to be significantly increased in cases compared to controls (p<0.0001) , this is in agreement with previous research findings which have reported increased oxidative stress in PCOS women irrespective of their BMI. [14][15][16] Oxidative stress was previously linked to obesity commonly seen in these PCOS women. 17,18 Oxidative stress has been implicated in a number of diseases such as cardiovascular disease, neurological disease, malignancies, renal disease, diabetes, inflammatory problems, skin diseases, aging, respiratory diseases, liver diseases and different types of viral infections.…”
mentioning
confidence: 99%